Temporal changes in zooplankton assemblage and the complex role of aquatic invasive species in the Ohio River, USA - Johnston, Samuel; Shepta, Erin; Arantes, Caroline C.; Murry, Brent (Frontiers in Environmental Science, 2026)
IntroductionZooplankton are critical components of aquatic food webs that transfer pelagic primary production to higher trophic levels. Nearly all fishes rely on zooplankton during their early life history, and many species remain planktivorous throughout their lives, yet zooplankton assemblages are vulnerable to anthropogenic stressors, especially invasive species, and are frequently understudied. Here we examine zooplankton assemblage changes occurring between sampling periods in 1991–1992 and 2021–2022 (a 30-year period) and a more robust analysis of contemporary assemblage change relative to the introduction of aquatic invasive species in the Ohio River, U.S.A.MethodsZooplankton were sampled in 8 navigation pools (reaches between locks and dams) in the Ohio River in 2021 and 2022 and (1) qualitatively compare these contemporary samples to historic published data from 1991–1992 and (2) analyze the contemporary data using multivariate statistics to evaluate the impact of invasive carps (silver, Hypophthalmichthys molitrix and bighead, H. nobilis) across a gradient of carp density.ResultsThere were notable changes to the zooplankton community from samples taken in 1991–92 to 2021–22, including a shift in large-bodied zooplankton from cladocerans to copepods and among small-bodied zooplankton invasive dreissenid mussel veligers largely replaced rotifers. Peak zooplankton density also advanced a month earlier in contemporary samples relative to the historic peak. Invasive carp have not yet had a measurable impact on the Ohio River zooplankton assemblage.Discussion and ConclusionChanges in the zooplankton assemblage were substantial and included taxa-specific phenological shifts that culminated in total assemblage density peak advancing a month earlier relative to historic timing. There were also changes in dominance in both large-bodied and small-bodied taxa. These changes are more consistent with changes observed in other systems relative to climate change and dreissenid mussel invasions than with invasive carps. Contrary to many other rivers in the Mississippi River basin invaded by silver and bighead carp, we observed little to no effect of invasive carps, though it will be important to continue monitoring zooplankton as the carp invasion advances.